Experimental investigation on local scour around spill-through spur dikes - Couto, L. T. (2015)
An experimental study on local around a spill-through spur dike has recently started in laboratory flume at the National Laboratory of Civil Engineering (LNEC) in Lisbon. The main objectives of this paper are the presentation of results, the check of existing literature on maximum scour depth and the characterisation of scour holes in their horizontal extend. Two sets of runs for uniform flow regime, corresponding to two different mixtures of river sand, are discussed. Experiments were made under live-bed and with clearwater conditions, for which different equations, obtained by multiple regression analysis, are suggested allowing the prediction of the maximum scour depth. A tentative relation for the width of the scour holes is also presented.